New developments in the administrative law enforcement of CCG: from the perspective of the implementation of CGP - Guo, Jianglan; Fu, Shuju; Shi, Yewei (Frontiers in Marine Science, 2025)
China established the China Coast Guard (CCG) in 2013. China promulgated China Coast Guard Law (CCGL) in 2021, which formally conferred on CCG the functions of maritime security and defense, maritime administrative law enforcement (MALE), and maritime crime investigation. In 2024, CCG revised the Directory of Maritime Administrative Law Enforcement Matters by China Coast Guard (CGD) and promulgated Provisions on Administrative Law Enforcement Procedures of Coast Guard Agencies (CGP). These three laws and regulations are most closely related to MALE of CCG, and with other laws and regulations related to MALE, they constitute a system of norms for MALE of CCG. This article reviews and summarizes the development history of MALE system of CCG, examines its MALE normative system in detail, and analyses the nature and content of CGP in depth. It then suggests ways to improve the system’s inadequacies.